(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Background: Chia (Salvia hispanica L.) seeds are used widely because of its nutritional value, antioxidant and antibacterial activity against various microorganisms but there are no studies that relate the antibacterial activity of Chia seeds against periodontal pathogens. Hence, this study aimed to determine the antimicrobial activity of Chia seeds extract on Porphyromonas gingivalis, Fusobacterium nucleatum and Aggregatibacter actinomycetemcomitans. Materials and Methods: Extract of Chia seeds in ethanol and distilled water were obtained by cold maceration. The crude residue was obtained by evaporation at room temperature. The antimicrobial efficacy of Chia seeds in all extracts were assessed against oral microorganisms by finding out zone of inhibition and minimal inhibitory concentration. Results: Chia seeds (Salvia hispanica) in ethanol and distilled water were found to be effective against A.actinomycetamcmitans, P.gingivalis and F.nucleatum by highest zone of inhibition being 18mm for aqueous extract of Chia seeds against A.actinomycetamcomitans. Minimum inhibitory concentration for aqueous extract of Chia seeds for A.actinomycetamcomitans and P.gingivalis was established at 50% and for F.nucleatum at 12.5%.The minimum inhibitory concentration of the ethanolic extract of Chia seeds for A.actinomycetamcomitans, P.gingivali and F.nucleatum was 12.5%, 6.25% and 50 % respectively. Conclusion: From results of the study, it is suggested that an ethanolic and aqueous extract of Chia seeds (S.hispanica) has antimicrobial activity against P. gingivalis A. actinomycetemcomitans and F.nucleatum.